A regional foresight process to cope with demographic change: future radar 2030 ( Zukunftsradar 2030 ). (16th October 2012) - Cuhls, Kerstin; Kolz, Heinz; Hadnagy, Christoph M.
This paper describes a foresight process that addresses social change and its impacts. Future Radar 2030 is a foresight process, in which tools from foresight are applied to work out scenarios and perform a survey. In combination with future workshops, the foresight process and its results have a direct impact on the stakeholders of a German federal state. It, therefore, has implications for society in general, but also for the innovation system. The paper describes the background (demographic change) and the tools from forecasting and foresight that were combined to work out relevant issues. It argues that even a 'small' regional foresight activity has an impact and changes some path of thinking.